Women, divorce and Islam in Kedah - Hassan, Sharifah Zaleha Syed (Sojourn, 1986)
Islamic marriage and divorce law elevates the status of women by virtue of the fact that women are treated as legal entities separate from and independent of the kin group to which they belong. The right that Islam grants to women to secure divorce also enables them to get out of a difficult marriage situation. However, divorce can be a moral as well as a society problem. This study highlights some of the problems that Malay Muslim women face, not after they have been divorced, but when they appeal to the religious authority for a divorce. (DÜI-Sen)